The place of total testosterone in the etiology of pilonidal sinus disease - Kanlioz, Murat; Karatas, Turgay; Ekici, Ugur; Tatli, Faik (Annals of Medical Research, 2021)
Aim: There are lots of factors accused in the etiology of SPSD. One of those factors is hypertrichosis. Hypertrichosis is increased by high levels of testosterone. In our clinical practices, we observe the secondary effects of high testosterone levels in those with SPSD. Hence, we intended to analyze the correlation between testosterone and SPSD.Material and Methods: The first 200 patients who applied to General Surgery Clinic at Malatya State Hospital and were diagnosed with SPDS, were included in the study after being informed of our research and signing the informed consent form. The total testosterone (TT) levels of the patients were measured and recorded along with their demographic data. Also, a control group was formed of male and female patients without SPSD having the same demographic characteristics, whose TT levels were also subsequently recorded. The data from control and study groups were then compared and analyzed.Results: Of the 200 patients included in the study, 43 (21.5%) were female and 157 (78.5%) were male. Their overall mean age was 24.13±7.04 years and the median age was 22 years (min:14- max:50). The male-to-female ratio was 3.65. The rate of females and males who had high levels of TT was significantly higher than that of the control group (p0.001). Conclusion: We recommend measuring serum TT levels of patients who apply to hospital for SPSD. SPSD might be the first visible ring of the chain of diseases characterized by high levels of TT.
Keywords: Etiological factors; pilonidal sinus disease; testosterone